A New Dynamic Response to Therapy Assessment in Postoperative Patients With Low-Risk Differentiated Thyroid Cancer Treated Without Radioactive Iodine - Dong, Ping; Wang, Li; Xiao, Liu; Yang, Liu; Huang, Rui; Li, Lin (Frontiers in Oncology, 2021)
Background: Total thyroidectomy (TT) or lobectomy without radioactive iodine (RAI) is becoming a common management for patients with low-risk differentiated thyroid cancer (DTC). However, the assessment of response to therapy for these patients remains controversial. The aim of this study was to propose and validate a new dynamic evaluation strategy to assess the response to therapy in patients with low-risk DTC treated with TT or lobectomy but without RAI. Methods: We performed a retrospective analysis of 543 adult patients with low-risk DTC who underwent TT or lobectomy without RAI therapy. Follow-up consisted of trends of serum thyroglobulin (Tg), anti-thyroglobulin antibody (TgAb) levels and neck ultrasonography (US) were conducted every 6–24 months. Response to therapy assessments were defined as excellent response, biochemical incomplete response, structural incomplete response, and indeterminate response according to the follow-up findings. Results: At a median follow-up of 51 months (range 33–66 months), 517 (95%) had excellent response, while the other 26 had either biochemical incomplete response (an increasing trend of suppressed serum Tg levels, n=9; an increasing trend of TgAb levels, n=3) or indeterminate response (a stable or decreasing trend of suppressed serum Tg levels, but a stable positive trend of TgAb levels, n=14). No patients had structural incomplete response or no deaths related to thyroid cancer. The risk of incomplete response was significantly higher in lobectomy than in TT (p<0.001). Conclusion: Our study proposed and validated a new dynamic response to therapy assessment depending on trends of suppressed serum Tg, TgAb levels, and neck US findings which could be an appropriate tool for postoperative follow-up in low-risk DTC patients without RAI therapy. Our findings provided further evidence to support no routine recommendation of RAI after surgery in low-risk DTC.